Comparison of Hip Abductor and Adductor Muscle Strength in Taekwondo and Non-taekwondo Practitioners - Seet Jia Sheng; Fachry Ambia Tandjung; Marietta Shanti Prananta (Althea Medical Journal, 2016)
Background: Taekwondo is an empty hand combat that entails the use of the whole body. Spinning and turning kicks are the proper way of kicking in taekwondo which allow one to maximally perform the hip abductor and adductor muscles simultaneously. To measure the hip abductor and adductor muscles of Taekwondo and Non-taekwondo practitioners, Hand-Held Dynamometer (HHD) is used. This study aimed to compare the hip abductor and adductor muscles strength in Taekwondo and Non-taekwondo practitioners.